Data supporting "Online optimisation and active control of the cure process of thick composite laminates" - Tifkitsis, Konstantinos; Skordos, Alexandros A. (Cranfield University, 2023)
The dataset comprises experimental data, and modelling and simulation results reported in the paper titled ‘Online optimisation and active control of the cure process of thick composite laminates’ published in Journal of Manufacturing Processes (2023). The dataset is organised into 5 files: - ‘Kinetics-DSC.xlsx’ contains the experimental DSC curves, after integration for the calculation of degree of cure evolution, and the corresponding cure kinetics modelling results. The file ia organised in two worksheets - ‘Dynamic’ reports the results of the one dynamic cure experiment and ‘Isothermal’ reports the results of the four isothermal experiments used in the analysis. - ‘Tg-MDSC.xlsx’ contains the MDSC specific heat capacity measurements and the corresponding model results for three isothermal experiments in worksheet ‘Specific heat capacity’ and the glass transition temperature values measured for partially cured samples alongside the corresponding glass transistor temperature evolution model in worksheet ‘Tg.’ - ‘FE model validation.xlsx’ contains the cure simulation validation trial results using a flat panel. The results are organised into two worksheets – ‘Temperature’ reports the experimental and simulation temperature as a function of time for 3 locations in the component and ‘Degree of cure’ the corresponding degree of cure results. - ‘Cable cure.xlsx’ reports the results of the active control trial for the cure of a cable. Worksheet ‘Active control trial’ reports the setpoint evolution and the surface and centre temperatures measured, alongside the corresponding degree of cure and glass transition evolution. Worksheet ‘Standard profile simulation’ reports the simulation results for the nominal cure profile. - Multi objective optimisation.xlsx presents the Pareto (temperature overshoot versus cure time) front obtained from offline optimisation for a two-cure dwell profile using an exhaustive search alongside the values of cure time and temperature overshoot for the nominal cure profile and the actively controlled process.
Keywords: Cure; Process monitoring; Automation; Process optimisation; Composite and Hybrid Materials; Manufacturing Processes and Technologies (excl. Textiles)